PENGARUH INTERVENSI TAHU KEDELAI HITAM KAYA SERAT TERHADAP GLUKOSA DARAH DAN INFLAMASI RESPONDEN DIABETES TIPE 2 - Nela Eska Putri; Fransiska R. Zakaria; Endang Prangdimurti; Nanda Triandita (Jurnal Teknologi dan Industri Pangan, 2016)
Type 2 diabetes mellitus (T2DM) subjects have a hyperglycemia condition. Hyperglycemia can cause oxidative stress that trigger glucose autooxidation and reactive oxygen species (ROS). ROS also triggers the inflammation and induces the cytokine signalling from cells and body tissues, such as interleukin and prostaglandin enzyme (COX-2). The purpose of this research was to analyze the effect of dietary fiber rich-tofu from black soybean (DFT) on bloods glucose and inflammations of T2DM patients. Intervention group (n=9) was given 80 grams DFT during 30 days and control group (n=9) was not. Blood collections were conducted before and after intervention by certified nurses for all groups for analysis in the laboratory. Fasting Blood Glucose (FBG) was measured by glucometer, while the plasma was analyzed with ELISA to measure the optical density value of IL-6 and COX-2 enzyme. Consumption of DFT resulted in the decline of the optical density of IL-6 value (p=0.00), but DFT could not reduce the FBG and optical density of COX-2 enzyme (p=0.22 and p=0.51). Therefore DFT can be considered as an effective food for reduction of T2DM inflammatory.